Niedobory neoawangardy: Połamany ludzik Rolanda i Nicolasa Toporów - Kornhauser, Jakub (Przestrzenie Teorii, 2024)
An article devoted to the categories of lack, deficiency, disruption and deformation in The Broken Little Man by Roland and Nicolas Topor in the context of neo-avant-garde activities and the theory of surrealism. The problems of visual poem collages and their spatial values, unfinishedness as a formula organizing the existence of the text, as well as distortions as defense mechanisms are discussed.